2018
DOI: 10.1259/dmfr.20170459
|View full text |Cite
|
Sign up to set email alerts
|

Fibrosarcoma arising in the paranasal sinus: a clinicopathological and radiological analysis

Abstract: Paranasal sinus fibrosarcomas should be included in the differential diagnosis when a sinonasal neoplasm appears as a well- or ill-defined unilateral large irregular mass with characteristic mild hypointensity on T weighted MR images and shows expansive or osteolytic bone destruction and a marked heterogeneous delayed contrast-enhancement pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…When suspecting PNFS, there are particular findings found on certain modalities that may rule in or out other diagnoses on the differential [35]. One study identified the common CT and MRI features seen in patients with confirmed PNFS [5]. This particular study confirmed that PNFS commonly presents as a solitary lobulated or irregular heterogeneous mass, with either well-or ill-defined margins.…”
Section: Diagnostic Methodsmentioning
confidence: 89%
See 3 more Smart Citations
“…When suspecting PNFS, there are particular findings found on certain modalities that may rule in or out other diagnoses on the differential [35]. One study identified the common CT and MRI features seen in patients with confirmed PNFS [5]. This particular study confirmed that PNFS commonly presents as a solitary lobulated or irregular heterogeneous mass, with either well-or ill-defined margins.…”
Section: Diagnostic Methodsmentioning
confidence: 89%
“…In routine clinical practice, paranasal fibrosarcoma is commonly misdiagnosed as other neoplasms due to its rarity and non-specific symptomatology. Therefore, it is critical to be familiar with the imaging features that differentiate paranasal fibrosarcoma from other malignancies [5]. Additionally, the rarity of the disease and the relatively few studies within the literature examining the imaging characteristics of PNFS continue to make the preoperative diagnosis of PNFS a challenge [5].…”
Section: Diagnostic Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patel et al analyzed 51 sinonasal fibrosarcoma patients from the SEER database. They found that the disease-specific survival rate of patients treated with surgery was better than patients treated with primary radiotherapy alone [ 35 , 36 ]. However, there has been no evaluation of postoperative prognosis in patients with fibrosarcoma.…”
Section: Discussionmentioning
confidence: 99%